2020
DOI: 10.3390/ijerph17238963
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Noise: Auditory and Non-Auditory Consequences

Abstract: Occupational noise exposure accounts for approximately 16% of all disabling hearing losses, but the true value and societal costs may be grossly underestimated because current regulations only identify hearing impairments in the workplace if exposures result in audiometric threshold shifts within a limited frequency region. Research over the past several decades indicates that occupational noise exposures can cause other serious auditory deficits such as tinnitus, hyperacusis, extended high-frequency hearing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 123 publications
0
38
0
7
Order By: Relevance
“…Rather, they are designed to protect a substantial portion of professional noise-induced hearing loss while maintaining a feasible cost–benefit ratio. There is also a growing awareness in the population that noise exposure, although mild, can contribute to a number of other auditory and non-auditory consequences, which may not be identified in hearing protection monitoring programs [ 28 ]. The development of audiological technology and the gradual availability of high-frequency audiometry could protect against hearing loss caused by noise, especially in younger people.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, they are designed to protect a substantial portion of professional noise-induced hearing loss while maintaining a feasible cost–benefit ratio. There is also a growing awareness in the population that noise exposure, although mild, can contribute to a number of other auditory and non-auditory consequences, which may not be identified in hearing protection monitoring programs [ 28 ]. The development of audiological technology and the gradual availability of high-frequency audiometry could protect against hearing loss caused by noise, especially in younger people.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the biological effects of acute high level noise exposure mostly focused on the auditory damage, while the non-auditory effects were less studied. Studies have shown that stress response, cognitive and cardiovascular dysfunction are typical non-auditory effects of long-term exposure to occupational noise [ 5 , 24 , 25 , 26 ]. Do these effects exist in acute high level noise exposure?…”
Section: Discussionmentioning
confidence: 99%
“…These noise levels were above Table 1. Mean values and standard deviations of noise emission (dBA) in each parish of Lisbon for each reference period (diurnal, evening and nocturnal) the legally established limit (Decree-Law 146/2006), which define an exposure limit value of 65 dB for daytime noise and 55 dB for nocturnal noise, and the recent World Health Organization guidelines for environmental noise in the European region [36]. Although we did not find a correlation between the factors, these high noise levels observed throughout the day could lead to an increase in negative cardiovascular and metabolic health outcomes in the future [37].…”
Section: Discussionmentioning
confidence: 99%